Dinamika Persepsi Publik dalam Konflik Nelayan dan Penegakan Hukum Perikanan: Studi Analisis Wacana Digital - Gusnita, Riri (IAI Nasional Laa Roiba Bogor, 2025)
The conflict arising between small-scale fishers and fisheries law enforcement authorities represents a persistent socio-ecological dilemma within the framework of coastal governance, particularly in policy environments that prioritize environmental conservation through the enforcement of strict fishing regulations. This study investigates the complexities of public perceptions surrounding disputes between fishers and the Ministry of Marine Affairs and Fisheries (KKP), focusing on how law enforcement practices, environmental sustainability discourses, and fishers’ livelihood interests are articulated and contested within digital public arenas. This research adopts a field research approach, with data analyzed using NVivo 15, drawing on 211 public narratives related to fisheries law enforcement incidents. The findings indicate that public reactions are shaped not only by issues of regulatory compliance but also by perceptions of injustice, surges of social emotion, and the structural vulnerabilities faced by small-scale fishers. While concepts of environmental protection and sustainable fisheries management are acknowledged within public discourse, such themes are often subordinated to livelihood security imperatives and demands for social justice. This study argues that fisheries conflicts cannot be comprehensively understood solely through an institutional legal framework; rather, they must be examined as social phenomena intrinsically linked to collective emotions, identity, and public trust in governmental institutions. These insights enrich the discourse on socio-ecological governance by underscoring the need for participatory, communicative, and socially legitimized law enforcement practices that reconcile marine conservation objectives with the socio-economic resilience of coastal communities.